2005
DOI: 10.1074/jbc.m504943200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of RelA/p65 on Serine 536 Defines an IκBα-independent NF-κB Pathway

Abstract: The association of the NF-B p65/p50 dimer with IB␣ plays a pivotal role in regulating its nuclear translocation and gene transcription. In addition, serine phosphorylation at various sites of the p65 subunit has been shown to be important in initiating transcription. Here we demonstrate that the regulation of nuclear translocation of p65 phosphorylated at serine 536 is not dependent on IB␣. Stimulation of either Jurkat or normal human T cells resulted in the nuclear translocation of phospho-p65 (Ser 536 ). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
293
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(313 citation statements)
references
References 44 publications
15
293
3
Order By: Relevance
“…Namely, the S525P mutation affects REL's transactivating ability on the SOD2 and 3X-kB site promoters in different ways: REL-S525P induces decreased transactivation of the SOD2 promoter, but increased transactivation of the 3X-kB site promoter. Similar promoter context variability has also been seen when the IKK site Ser536 in RelA is mutated; that is, RelA-S536A transactivates the intercellular cell adhesion molecule (ICAM)-1 promoter more efficiently than wild-type RelA, but activates the IL-8 promoter weaker than RelA (Sasaki et al, 2005).…”
Section: Discussionmentioning
confidence: 69%
“…Namely, the S525P mutation affects REL's transactivating ability on the SOD2 and 3X-kB site promoters in different ways: REL-S525P induces decreased transactivation of the SOD2 promoter, but increased transactivation of the 3X-kB site promoter. Similar promoter context variability has also been seen when the IKK site Ser536 in RelA is mutated; that is, RelA-S536A transactivates the intercellular cell adhesion molecule (ICAM)-1 promoter more efficiently than wild-type RelA, but activates the IL-8 promoter weaker than RelA (Sasaki et al, 2005).…”
Section: Discussionmentioning
confidence: 69%
“…Also, lymphotoxin ␤ induces NIK-and IKK␣-mediated p65 transcriptional activity through p65 S536 phosphorylation (29). Furthermore, phorbol 12-myristate 13-acetate and ionomycininduced p65 S536 phosphorylation is not inhibited by I B␣ expression, which is characteristic of the noncanonical pathway (49). Thus, the IRAK1 dependence of TES1-mediated NF-B activation is likely because of a need for p65 phosphorylation for efficient transcriptional enhancement by p65͞p52 complexes.…”
Section: Discussionmentioning
confidence: 88%
“…4 In the lymphoblastic lymphoma cell line Jurkat and in primary T-cell lymphocytes, p65 is constitutively phosphorylated at Ser536. 5 In this work we have isolated leukemic blasts obtained from two CD7/CD56-positive AML and seven conventional AML blasts. Both of the CD7/CD56 AML patients' samples were collected at the time of the diagnosis.…”
mentioning
confidence: 99%
“…In a recently published work, it has been demonstrated that in Jurkat cells; and in primary T-cell lymphocyte, p65 is constitutively phosphorylated at Ser536. 5 Upon stimulation, phospho-p65 translocates into the nucleus where it mediates the transcription of a putative specific set of genes, probably different with respect to those activated by conventionally activated p65. [4][5] In Figure 1b, Jurkat cells extract has been considered as an example of known phosphorylated p65 expressing cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation